PPIA, HRPT1, and PGK1 genes as the appropriate combination for RT-qPCR normalization in alveolar and femoral bone remodeling in olanzapine-treated rats - Disha-Ibrahimi Saranda; Drevenšek Gorazd; Drevenšek Martina; Marc Janja; Žitnik Irena Prodan (Acta Pharmaceutica)
Reliable gene expression analysis in bone remodeling studies requires an appropriate selection of internal controls, i.e. stable reference genes for the normalization of quantitative real-time PCR (RT-qPCR), the most common method used for quantifying gene expression measurements. Even the most widely used reference genes can have variable expression under different experimental conditions, or in different tissue types or treatment regimes, so selecting appropriate controls is a key step in ensuring reliable results. The aim of this research was to identify the most stable reference gene(s) for the study of olanzapine modulated bone remodeling in rats. RNA was isolated from the maxillary alveolar and femoral bones of olanzapine or placebo-treated Wistar rats and transcribed to cDNA. The expression of 12 candidate reference genes was assessed by RT-qPCR. Their expressions were analysed using GeNorm, NormFinder, BestKeeper and delta Ct algorithms, and by the comprehensive ranking method. PPIA, HRPT1 and PGK1 were the most stably expres sed reference genes and the combination of the three genes was optimal for normalization. This study is the first to identify the optimal reference genes for research in olanzapine-exposed rats, which serve as a pivotal benchmark for enhancing the accuracy and reliability of future RT-qPCR expression in bone studies.